Age-Dependent Modifications of AMPA Receptor Subunit Expression Levels and Related Cognitive Effects in 3xTg-AD Mice - Cantanelli, Pamela; Sperduti, Samantha; Ciavardelli, Domenico; Stuppia, Liborio; Gatta, Valentina; Sensi, Stefano Luca (Frontiers in Aging Neuroscience, 2014)
GluA1, GluA2, GluA3, and GluA4 are the constitutive subunits of AMPA receptors (AMPARs), the major mediators of fast excitatory transmission in the mammalian central nervous system. Most AMPARs are Ca2+-impermeable because of the presence of the GluA2 subunit. GluA2 mRNA undergoes an editing process that results in a Q to R substitution, a key factor in the regulation of AMPAR Ca2+-permeability. AMPARs lacking GluA2 or containing the unedited subunit are permeable to Ca2+ and Zn2+. The phenomenon physiologically modulates synaptic plasticity while, in pathologic conditions, leads to increased vulnerability to excitotoxic neuronal death. Given the importance of these subunits, we have therefore evaluated possible associations between changes in expression levels of AMPAR subunits and development of cognitive deficits in 3xTg-AD mice, a widely investigated transgenic mouse model of Alzheimer’s disease. With qRT-PCR, we assayed hippocampal mRNA expression levels of GluA1-4 subunits occurring in young [3 months of age (m.o.a.)] and old (12 m.o.a) Tg-AD mice and made comparisons with levels found in age-matched wild type (WT) mice. Efficiency of GluA2 RNA editing was also analyzed. All animals were cognitively tested for short- and long-term spatial memory with the Morris Water Maze (MWM) navigation task. 3xTg-AD mice showed age-dependent decreases of mRNA levels for all the AMPAR subunits, with the exception of GluA2. Editing remained fully efficient with aging in 3xTg-AD and WT mice. A one-to-one correlation analysis between MWM performances and GluA1-4 mRNA expression profiles showed negative correlations between GluA2 levels and MWM performances in young 3xTg-AD mice. On the contrary, positive correlations between GluA2 mRNA and MWM performances were found in young WT mice. Our data suggest that increases of AMPARs that contain GluA1, GluA3, and GluA4 subunits may help in maintaining cognition in pre-symptomatic 3xTg-AD mice.